PENGUATKAN IDENTITAS NASIONAL & CINTA TANAH AIR MAHASISWA MELALUI PEMBIASAAN PEMUTARAN LAGU "INDONESIA RAYA" - Mariyani M; Primandha Sukma Nur Wardhani; Makarius Erwin Bria (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2025)
This research aims to explore how the habit of playing the song "Indonesia Raya" in higher education can strengthen national identity and instill the character of love for the homeland among students. Using a qualitative approach with a case study design, data was collected through participatory observation, in-depth interviews, and documentation of campus activities involving the national anthem. Data analysis in this study was carried out through a narrative descriptive approach to the results of in-depth interviews, participatory observations, and documentation of "Indonesia Raya" song playback activities at Primagraha University. The informants in this study were 5 people from different study programs at FKIP and FEB Primagraha University.  The results of the study show that the playing of the song "Indonesia Raya" is not only symbolic, but has a transformative power on students' perspective on the nation, history of struggle, and national values. Certain lyrics evoke a spirit of unity, pride, and responsibility to contribute to the development of the nation. This song also acts as a national identity booster and a source of motivation for students to behave positively in campus and social life. Instilling the character of love for the homeland through national music is a relevant strategy in the era of globalization, where national values need to be integrated into academic and digital spaces creatively. Through meaningful habituation, the national anthem can be a medium of character education that is alive and has a real impact.